2015
DOI: 10.5194/acp-15-2883-2015
|View full text |Cite
|
Sign up to set email alerts
|

Standard climate models radiation codes underestimate black carbon radiative forcing

Abstract: Abstract. Radiative forcing (RF) of black carbon (BC) in the atmosphere is estimated using radiative transfer codes of various complexities. Here we show that the two-stream radiative transfer codes used most in climate models give too strong forward scattering, leading to enhanced absorption at the surface and too weak absorption by BC in the atmosphere. Such calculations are found to underestimate the positive RF of BC by 10 % for global mean, all sky conditions, relative to the more sophisticated multi-stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…First, the OsloCTM2 results are derived using an eight‐stream radiative transfer model, while the radiation scheme in CAM4 is two‐stream only. This was recently found to cause a 10% difference for global, annual mean modeled BC RF due to multiple scattering over high‐albedo surfaces [ Myhre and Samset , ]. For Figure a, we performed a calculation with the OsloCTM2 code in two‐stream mode.…”
Section: Discussionmentioning
confidence: 99%
“…First, the OsloCTM2 results are derived using an eight‐stream radiative transfer model, while the radiation scheme in CAM4 is two‐stream only. This was recently found to cause a 10% difference for global, annual mean modeled BC RF due to multiple scattering over high‐albedo surfaces [ Myhre and Samset , ]. For Figure a, we performed a calculation with the OsloCTM2 code in two‐stream mode.…”
Section: Discussionmentioning
confidence: 99%
“…The 1‐D radiative transfer equation was solved using a six‐stream discrete ordinates radiative transfer solver developed by Stamnes et al []. Myhre and Samset [] showed that the commonly used two‐stream codes lead to approximately 15% underestimation in absorbing aerosol DRE. Surface type and albedo were obtained from the International Geosphere‐Biosphere Programme library, which contains 20 surface types [ Loveland and Belward , ].…”
Section: Methodsmentioning
confidence: 99%
“…Elevating small sensors above ground level has significant benefits for atmosphere physics, especially when it comes to aerosol research. Complex interactions between aerosols and solar radiation, together with very limited measurement options of vertical profiles of aerosols' optical and microphysical properties, make understanding and modeling Earth's climate difficult (Bond et al 2013;IPCC 2013;Koch and Del Genio 2010;Myhre and Samset 2015). Columnar integrated data are available for many properties, but it is important to remember that for some aerosols, such as absorption of black carbon (BC), vertical distribution is even more important than total columnar values (Samset and Myhre 2011;Samset et al 2013;Zarzycki and Bond 2010;Cook and Highwood 2004).…”
Section: Introductionmentioning
confidence: 99%